Ayya's Accounts : A Ledger of Hope in Modern India - Pandian, Anand; Mariappan, M. P., 1919- (Book collections on Project MUSE., 2014)
Ayya's Accounts explores the life of an ordinary man-orphan, refugee, shopkeeper, and grandfather-during a century of tremendous hope and upheaval. Born in colonial India into a despised caste of former tree climbers, Ayya lost his mother as a child and came of age in a small town in lowland Burma. Forced to flee at the outbreak of World War II, he made a treacherous 1,700-mile journey by foot, boat, bullock cart, and rail back to southern India. Becoming a successful fruit merchant, Ayya educated and eventually settled many of his descendants in the United States. Luck, nerve, subterfuge ...